Assessing Companies Through CSR and Profitability in Manufacturing Sector Companies in Indonesia - Hisar Sirait; Rita Eka Setianingsih; Erna Sari; Sylvia Sari Rosalina; Supriyanto (GoAcademica Research & Publishing, 2022)
The purpose of this study is to examine the impact of Corporate Social Responsibility (CSR) on company value, with profitability as a moderating variable, for manufacturing sector firms listed on the Indonesia Stock Exchange during the period 2015-2019. This study employs quantitative methodologies, such as testing numerical data and statistical tests. The population of this study consists of all Indonesia Stock Exchange-listed manufacturing firms (IDX). This study uses a strategy of purposive sampling based on specific criteria to acquire representative data from 26 companies. Through the website www.idx.co.id, secondary company data in the form of financial reports and annual reports of manufacturing businesses listed on the Indonesia Stock Exchange are collected. The results of previous study indicate that CSR has a positive and considerable impact on the value of a company. Profitability has a favorable and substantial effect on the value of a company. Profitability can moderate the correlation between CSR and enterprise value. This demonstrates that the degree of company earnings can improve the link between corporate social responsibility and firm value.